Enhancing Personalized Learning and Engagement Through Technology in Modern Education - Hardianti, Hardianti; Risnawati, Risnawati; Ananta, Nurasti (Educia Journal, 2024)
This study investigates the role of technology in empowering students through personalized learning, enhanced engagement, and collaboration in educational settings. The integration of technology into education has transformed traditional learning paradigms, enabling tailored approaches that cater to individual learning styles, needs, and paces. Through adaptive learning platforms, digital tools, and interactive content, technology fosters self-directed learning and critical thinking, encouraging students to take ownership of their educational journey. Moreover, the study highlights the role of technology in facilitating collaboration through virtual classrooms, group projects, and real-time communication tools, which enhance engagement and foster a sense of community among learners. However, significant challenges persist, particularly concerning equity and access. Disparities in internet connectivity, availability of devices, and digital literacy continue to create a divide, limiting the potential of technology to empower all students. This research underscores the importance of addressing these barriers to ensure inclusivity and equitable access to technology-driven education. It concludes by advocating for policies and practices that prioritize accessibility, teacher training, and sustainable infrastructure to create an educational ecosystem where technology serves as a tool for empowerment rather than exclusion. The findings contribute to the growing body of literature on technology-enhanced learning and provide actionable insights for educators, policymakers, and stakeholders seeking to leverage technology for inclusive education.